Mindfulness and burnout among competitive adolescent tennis players - Walker, SP (South African Journal of Sports Medicine, 2013)
Background. Burnout among adolescent athletes is a cause for concern. However, little is known about the intrapersonal factors that may be related to burnout in this population. Objectives. To explore the relationship between burnout and mindfulness among competitive adolescent tennis players. Methods. Competitive adolescent tennis players (N=104; mean age 16 years) completed measures of mindfulness and athlete burnout. Correlations were calculated with regard to mindfulness and burnout. A one-way multivariate analysis of variance (MANOVA) was conducted to determine whether athletes assigned to three levels of mindfulness (high, moderate and low) differed significantly with regard to burnout. Results. Mindfulness exhibited significant negative correlations with global burnout, emotional/physical exhaustion, reduced sense of accomplishment and sport devaluation. The results of the MANOVA indicated that individuals in the three mindfulness groups (high, moderate and low) reported significantly different levels of burnout. Post hoc analyses revealed that participants in the high mindfulness group reported a significantly lower sense of reduced accomplishment and global burnout than participants in the low mindfulness group. In addition, participants in the low mindfulness group reported significantly higher levels of global burnout than individuals in the high and moderate mindfulness groups. Conclusion. Mindfulness appears to be negatively related to athlete burnout among competitive adolescent tennis players. Furthermore, athletes reporting different levels of mindfulness exhibit differing levels of burnout. The potential protective effect of mindfulness with regard to burnout among adolescent athletes warrants further investigation.